Electroacupuncture for patients with irritable bowel syndrome: A systematic review and meta-analysis protocol. Issue 31 (August 2018) - Zhang, Yu; Li, Ziqing; Han, Fan
Abstract: Background: Irritable bowel syndrome (IBS) is a common functional intestinal disease characterized by chronic or recurrent abdominal pain, abdominal distension, constipation and diarrhea. Many IBS sufferers are usually present with poor quality of life for the abdominal discomfort, diarrhea, constipation, and other complaints. At present, the commonly used drug therapy for IBS in the Western clinic, such as antidiarrheal, laxative, gastrointestinal antispasmodic, often cannot get satisfying curative effect. Thus complementary therapies like electroacupuncture (EA) which may be effective to decrease patients' pain and fewer side-effects will be sought. EA, an innovative form of traditional acupuncture, is drawing more attention to the treatment of IBS due to its roles in symptom improvement. This systematic review protocol aims at describing a meta-analysis to critically evaluate the effectiveness and safety on EA for patients with IBS. Methods: We search Ovid MEDLINE, Ovid Embase, PubMed, the Cochrane Central Register of Controlled Trials (Cochrane Library), the Allied and Complementary Medicine Databases (AMED), China National Knowledge Infrastructure (CNKI) for random controlled trials EA for IBS from their inception to April 1, 2018. Two reviewers will independently screen studies for data extraction and assess the quality and risk of bias. RevManV5. 3 will be applied to data extraction. Risk of bias for each RCT will be assessed according to criteria by the Cochrane Handbook to evaluate the methodological quality. Results: This study will provide a high-quality synthesis of current evidence of effectiveness and safety on EA for patients with IBS. Conclusion: The conclusion of our systematic review will provide evidence to judge whether EA is an effective intervention for patient with IBS. PROSPERO registration number: PROSPERO CRD42018081610. Abstract : Supplemental Digital Content is available in the text